COVID‐19 in pediatric kidney transplantation: The Improving Renal Outcomes Collaborative. Issue 8 (11th February 2021) - Varnell, Charles; Harshman, Lyndsay A.; Smith, Laurie; Liu, Chunyan; Chen, Shiran; Al‐Akash, Samhar; Barletta, Gina‐Marie; Belsha, Craig; Brakeman, Paul; Chaudhuri, Abanti; Fadakar, Paul; Garro, Rouba; et al.
Abstract : There are limited data on the impact of COVID‐19 in children with a kidney transplant (KT). We conducted a prospective cohort study through the Improving Renal Outcomes Collaborative (IROC) to collect clinical outcome data about COVID‐19 in pediatric KT patients. Twenty‐two IROC centers that care for 2732 patients submitted testing and outcomes data for 281 patients tested for SARS‐CoV‐2 by PCR. Testing indications included symptoms and/or potential exposures to COVID‐19 ( N  = 134, 47.7%) and/or testing per hospital policy ( N  = 154, 54.8%). Overall, 24 (8.5%) patients tested positive, of which 15 (63%) were symptomatic. Of the COVID‐19‐positive patients, 16 were managed as outpatients, six received non‐ICU inpatient care and two were admitted to the ICU. There were no episodes of respiratory failure, allograft loss, or death associated with COVID‐19. To estimate incidence, subanalysis was performed for 13 centers that care for 1686 patients that submitted all negative and positive COVID‐19 results. Of the 229 tested patients at these 13 centers, 10 (5 asymptomatic) patients tested positive, yielding an overall incidence of 0.6% and an incidence among tested patients of 4.4%. Pediatric KT patients in the United States had a low estimated incidence of COVID‐19 disease and excellent short‐term outcomes. Abstract : This report from the Improving Renal Outcomes Collaborative describes SARS‐CoV‐2 testing characteristics, indications, and positivity rate along with the symptoms and clinical outcomes of COVID‐19 for pediatric kidney transplant patients across 22 centers in the United States.